A novel MS to SL vialess vertical transition for high‐performance substrate integrated filter. Issue 12 (17th October 2022) - Zhang, Xianfang; Feng, Linping; Zhu, Lei; Zhang, Xiaoping; Shi, Weimin; Zhang, Yongliang
Abstract: In this paper, a novel broadband microstrip‐to‐stripline (MS‐to‐SL) vialess vertical transition structure is presented and demonstrated. Firstly, the vialess vertical transition is introduced under two kinds of transmission lines and signal transmission between them through the slotline in the middle ground layer is realized. Then, the proposed vialess vertical transition structure is applied to build up a six‐pole broadband high selective bandpass substrate integrated filter with an equal ripple level. After that, for fascinating the design, its design method is analyzed, and design flow is given. Finally, the proposed filter is fabricated and measured. All the simulated and measured results match well with each other.